2018
DOI: 10.19082/7078
|View full text |Cite
|
Sign up to set email alerts
|

Student-related factors affecting academic engagement: A qualitative study exploring the experiences of Iranian undergraduate nursing students

Abstract: Background and aimAcademic engagement is an important indicator of quality of higher education. This study aimed to explain the experiences of undergraduate nursing students in terms of student-related factors affecting academic engagement.MethodsThis qualitative study was conducted in 2017 at Mashhad University of Medical Sciences in Iran. Data were collected using semi-structured interviews and focus groups with 7 and 16 undergraduate nursing students at Mashhad School of Nursing and Midwifery; respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
1
19
0
4
Order By: Relevance
“…Therefore, because more than half of nursing education takes place in clinical settings, the findings of these studies do not support the role of these strategies in increasing the academic engagement of nursing students in clinical education. In contrast, previous studies have shown that nursing students have greater motivation, both internally and externally, to learn clinical activities; therefore, they are more engaged in these activities [44,58].…”
Section: Miscellanea Learning Strategiesmentioning
confidence: 84%
“…Therefore, because more than half of nursing education takes place in clinical settings, the findings of these studies do not support the role of these strategies in increasing the academic engagement of nursing students in clinical education. In contrast, previous studies have shown that nursing students have greater motivation, both internally and externally, to learn clinical activities; therefore, they are more engaged in these activities [44,58].…”
Section: Miscellanea Learning Strategiesmentioning
confidence: 84%
“…Participants' experiences demonstrated that interest in learning was one factor that increased academic engagement, increased appeal towards subjects or educational content. Ghasemi et al (2018) study, showed that interest in, and intellectual and mental concentration on educational subjects, increased learning efforts, and ultimately contributed to greater and deeper learning. According to Joshi et al (2017), participants' suggestions to achieve high learning performance referred to consideration of learning styles and strategies like daily revision of topics, being regular and attentive during ward postings.…”
Section: Discussionmentioning
confidence: 98%
“…[4] For this, using best theory-based strategies to increase students' engagement has always been the main concern of Iranian nursing educators. [5] The possible reason could be the concept of student's engagement is ambiguous in the field of academic and clinical nursing education in Iran and limited research has been done on its definition, dimensions, and optimal strategies. [5] Therefore, many aspects need to be clear through a well-designed theory-based educational research, either qualitative or quantitative.…”
mentioning
confidence: 99%
“…[5] The possible reason could be the concept of student's engagement is ambiguous in the field of academic and clinical nursing education in Iran and limited research has been done on its definition, dimensions, and optimal strategies. [5] Therefore, many aspects need to be clear through a well-designed theory-based educational research, either qualitative or quantitative. [5] First, this concept should be theoretically analyzed and the conceptual framework for Iranian nursing students' clinical engagement needs to be developed.…”
mentioning
confidence: 99%
See 1 more Smart Citation